Dampak corporate social responsibility dan firm size terhadap firm value dengan profitabilitas sebagai variabel moderating - Elvando Pelupessy; Swarmilah Hariani (Jurnal Riset Manajemen dan Bisnis, 2022)
This research aimed to analyze the influence of corporate social responsibility and firm size on firm value with profitability as a moderating variable. The population of the research subject was companies listed on the LQ45 index in the period 2017-2019. The method of determining the sample in this study used a purposive sampling technique and obtained 57 sample observation data. This research is causal, and data analysis was done by moderation regression analysis using the SPSS version 25 program. The data analysis showed that corporate social responsibility had a negative and significant effect on firm value, firm size did not affect firm value, and profitability could not moderate the influence of corporate social responsibility. However, it could moderate the influence of firm size on firm value.